Hypertensive Disorder in Pregnancy: A Comparative Cross-Sectional Study of Maternal Characteristics in Urban and Rural Communities - Putri Mulia Sakti; Febti Kuswanti; Khuzaifah; Siti Jumhati; Sundari Fatimah (Napande: Jurnal Bidan, 2026)
Background: Hypertensive disorders of pregnancy remain a major contributor to maternal morbidity and mortality worldwide, affecting approximately 10% of pregnancies. Demographic and lifestyle factors play a crucial role in the development of hypertension during pregnancy, with evidence suggesting higher pregnancy-related mortality risks among women living in rural areas compared to urban settings. This study aimed to examine differences in risk factors for hypertensive disorders in pregnancy between pregnant women residing in urban and rural areas. Method: A cross-sectional study was conducted from March to September 2025 at two community health centers, one in an urban area (Depok, West Java) and one in a rural area (Poso Regency). The study population comprised pregnant women diagnosed with hypertension after 20 weeks of gestation. A total of 66 respondents were recruited using accidental sampling. Data were collected using a questionnaire adapted from the 2023 Indonesian Health Survey (maternal health section). Statistical analysis included the Kolmogorov–Smirnov test for normality and the Mann–Whitney test for group comparisons, with a significance level of p < 0.05. Ethical approval was obtained before data collection. Result: Of the 17 risk factors assessed, five showed significant differences between urban and rural respondents. These included parity (p = 0.021), history of chronic disease (p = 0.021), exposure to cigarette smoke (p = 0.001), physical activity (p = 0.008), and frequency of spicy food consumption (p = 0.012). Conclusion: Significant differences in maternal characteristics associated with hypertensive disorders of pregnancy were observed between urban and rural populations. These findings highlight the need for context-specific maternal health interventions that consider local demographic and lifestyle factors to improve maternal and perinatal outcomes